Chlorinated bis-indole alkaloids from deep-sea derived Streptomyces sp. SCSIO 11791 with antibacterial and cytotoxic activities - Song, Yongxiang; Yang, Jiafan; Yu, Jianchen; Li, Jie; Yuan, Jie; Wong, Nai-Kei; Ju, Jianhua (Journal of antibiotics, 2020)
Two new chlorinated bis -indole alkaloids, dionemycin ( 1 ) and 6-OMe-7′,7″-dichorochromopyrrolic acid ( 2 ), along with seven known analogs 3 – 9 , were isolated from the deep-sea derived Streptomyces sp. SCSIO 11791. Their structures were elucidated by extensive HRESIMS, and 1D and 2D NMR data analysis. In vitro antibacterial and cytotoxic assays revealed that, compound 1 , shows anti-staphylococcal activity with an MIC range of 1–2 μg/mL against six clinic strains of methicillin-resistant Staphylococcus aureus (MRSA) isolated from human and pig. Additionally, compound 1 displayed cytotoxic activity against human cancer cell lines NCI-H460, MDA-MB-231, HCT-116, HepG2, and noncancerous MCF10A with an IC 50 range of 3.1–11.2 μM. Analysis of the structure-activity relationship reveals that the chlorine atom at C-6″ could be pivotal for conferring their bioactivities, thus providing hints on chemical modifications on bis -indole alkaloid scaffold in drug design.